Breastfeeding satisfaction post hospital discharge and associated factors - a longitudinal cohort study of mothers of preterm infants - Jenny Ericson; Erik Lampa; Renée Flacking (BMC, 2021)
Abstract Background Mothers' satisfaction with breastfeeding is important for breastfeeding duration but rarely investigated in mothers of preterm infants. The aim of this study was to describe breastfeeding satisfaction and associated factors during the first year in mothers of preterm infants (gestational age < 37 weeks). Methods This longitudinal cohort study, based on secondary analysis data from a randomized controlled trial, included 493 mothers of 547 preterm infants. Data on breastfeeding duration and satisfaction, parental stress and attachment were collected at 8 weeks post discharge, and at 6 and 12 months after birth. Breastfeeding satisfaction was measured by the Maternal Breastfeeding Evaluation Scale. Descriptive statistics and linear mixed effect models were used when analyzing the data. Results During the first 12 months breastfeeding satisfaction increased in the mean summary scores and points in the dimensions "role attainment" and "lifestyle and maternal body image". In the dimension "infant growth and satisfaction", there was an increase in mean points from 6 to 12 months after birth, but not between 8 weeks after discharge and 12 months after birth. The findings also showed that partial and no breastfeeding, higher parental stress, and infant gestational age < 32 weeks were associated with decreased breastfeeding satisfaction. Older maternal age and greater maternal attachment were associated with increased maternal breastfeeding satisfaction. There were no associations between maternal breastfeeding satisfaction and maternal educational level, parity, multiple birth, or maternal birth country other than Sweden, during the first 12 months after birth. Conclusions Breastfeeding satisfaction was clearly associated with breastfeeding duration during the first year after birth. Breastfeeding satisfaction may be important to take into account when supporting breastfeeding and when designing interventions to support breastfeeding. Furthermore, these findings highlight the complexity of breastfeeding and emphasize the need for early and good support during neonatal care, so that mothers feel trust in themselves and their infant and in exclusive breastfeeding at discharge and in the first months thereafter. Trial registration The randomized controlled trial was registered NCT01806480 with www.clinicaltrials.gov on 2013-03-07.